PEMANFAATAN DANA KAMPUNG DALAM MENINGKATKAN PEMBANGUNAN KAMPUNG: (Studi Di Kampung Watiyai Distrik Tigi Timur Kabupaten Deiyai) - Angwarmas, Kornelis (SKETSA : Jurnal Ilmu-Ilmu Sosial, 2018)
This study aims to find out the extent of the use of village funds in the development of the village, along with the results of the use of village funds and how much community involvement in Watiyai Village, District of Tigi Timur, Deiyai ​​Region is in the development of the village. The research approach used is descriptive qualitative. By using data collection techniques through interviews with informants who are considered to have the potential to provide information about the use of village funds in the construction of Watiyai Village, Tigi Timur District, Deiyai ​​Region, also through observation and documentation of the results of utilization of village funds. The results showed that the Utilization of Village Funds in the Development of Watiyai Village in Tigi Timur District was not very effective yet. This can be proven by the number of development programs that have been realized even though they have not been so good, because there are still various obstacles that are quite influential to the development and use of the village funds. The same thing was also influenced by the weakness of community involvement in the implementation of village funds utilization in Watiyai Village, where the community participated in all activities village governments funded by village funds always ordered compensation for their involvement during village program development and policies until the implementation of these programs.